Short-, medium- and long-term results of the sling operations effectiveness and safety for urinary incontinence in women - O. B. Loran; A. V. Seregin; Z. A. Dovlatov (Вестник урологии, 2020)
Introduction. Sling urethropexy is considered the «gold standard» surgical treatment for stress urinary incontinence in women. However, the long-term results of such operations have not yet been fully studied.Purpose of the study. To evaluate the results of using various options for sling operations at different periods of postoperative follow-up.Materials and methods. In 698 women aged 42 - 68 years (median — 54 years) suffering stress incontinence were used 4 variants of sling operations according to the database of the S.P. Botkin City Clinical Hospital: TVT retropubic technique; transobturator technique TVT-O («inside-out»); transobturator technique TOT («outside-in»); mini sling system. The period of postoperative follow-up was 6 - 139 months (median 79 months). Evaluation of treatment results was carried out according to the following periods of postoperative follow-up: short-term (up to 1 year inclusive); mediumterm (a period from 1 to 5 years inclusive); long-term (over 5 years). The success of the treatment was determined by the criterion of the absence of urine involuntary loss during the cough test and the 1-hour pad test.Results. Treatment success in the entire sample of patients was 96.1% (671 / 698) for the short-term criterion, 93.1% (591 / 635) for the medium-term criterion and 86.2% for the long-term criterion (467 / 642). The effectiveness of short-term treatment after TVT was 97%, TVT-O — 95.8%, TOT — 96.2%, mini-sling system — 95.5%, in medium-term — 92.2%, 93.1%, 90.9% and 92.3%, respectively, for long-term — 87.1%, 86.2%, 85.2% and 85%, respectively. There were no significant differences between the indicated variants of sling operations in terms of treatment efficacy for all observation periods (p > 0.05). Intra and early postoperative complications were noted in 51 (7.3%) cases, late — in 79 (11.3%). There were no significant differences in the incidence of both categories of complications between the surgical techniques used (p > 0.05). Only surgical experience significantly affects the risk of recurrent urinary incontinence after surgery, early and late postoperative complications.Conclusions. The success of surgical treatment for stress urinary incontinence in women does not significantly depend on the type of sling surgery but depends mainly on the surgical experience. Therefore, it is advisable to use sling operations in hospitals with extensive experience in this area.